(untitled) (World Economics and Finance Bulletin, 2024)
In this article, the population depends on the economic culture in raising the business mindset, and the economic behavior of the population as a whole system is effectively covered. It has been scientifically analyzed that economic culture, production culture is a whole social system, and its use is effective only if it is implemented in a complex way.